1975
DOI: 10.1021/j100578a011
|View full text |Cite
|
Sign up to set email alerts
|

Densities and apparent molal volumes of some aqueous rare earth solutions at 25.deg.. III. Rare earth nitrates

Abstract: The densities of aqueous solutions of La(NOs)3, Pr(NC>3)3, Nd(NOs)3, Sm(N03)s, Gd(NOs)3, Tb(NOs)3, Dy(NOs)3, Ho(N03)s, Er(NOs)3, Yb(NC>3)3, and Lu(NOs)3 were determined from approximately 0.03 m to saturation at 25°with an accuracy of ±3 X 10-5 g/ml by a pycnometric method. The densities are represented with empirical equations. The apparent molal volumes were fitted to semiempirical equations and partial molal volumes were calculated. The partial molal volume data for the nitrate solutions are compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

1978
1978
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 5 publications
6
39
1
Order By: Relevance
“…Although [11] only reports parameters for equations which model the concentration dependences of the calculated apparent molar volumes rather than the experimentally determined densities, they are available as supplementary material from the American Chemical Society. However, measured densities are contained in the pycnometric study reported by Spedding et al [13]. The latter manuscript reports densities and apparent molar volumes for aqueous 3 (aq), in the concentration range of approximately 0.03 mol AE kg À1 to saturation and provides a useful comparison with V /,2 values reported in this manuscript.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Although [11] only reports parameters for equations which model the concentration dependences of the calculated apparent molar volumes rather than the experimentally determined densities, they are available as supplementary material from the American Chemical Society. However, measured densities are contained in the pycnometric study reported by Spedding et al [13]. The latter manuscript reports densities and apparent molar volumes for aqueous 3 (aq), in the concentration range of approximately 0.03 mol AE kg À1 to saturation and provides a useful comparison with V /,2 values reported in this manuscript.…”
Section: Resultsmentioning
confidence: 81%
“…Although there have been several previous studies which report apparent molar volumes and apparent molar heat capacities for aqueous rare earth nitrate solutions they have invariably been restricted to T = 298.15 K and p = 0.1 MPa [11][12][13][14]. In addition, it would appear that the only previous calorimetric heat capacity investigation performed on aqueous rare earth nitrates [14] utilised the technique of batch calorimetry that has previously been shown to lack the precision of the flow calorimetry procedure used in this study when investigating dilute aqueous solutions [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…(10,50) However, these properties then begin to show some gradual shifts in the location of the initial break from Nd 3+ (aq) to some higher atomic number R 3+ (aq) at higher molalities where water sharing between ions or increasing complex formation may partially alter the hydration trends. In contrast, for the R(NO 3 ) 3 (aq) solutions, this two-series effect has already started to disappear by m = 0.1 mol · kg −1 , (51) apparently as a result of formation of significant amounts of rare-earth nitrate complexes.…”
Section: (Aq) and R(so )mentioning
confidence: 89%
“…Spedding et al (51) gave plots of V m,2 − V • φ for the R(ClO 4 ) 3 (aq), RCl 3 (aq), and R(NO 3 ) 3 (aq) at T = 298.15 K, where R denotes La, Nd, Tb, and Lu. One of their plots shows that the molality dependences of V m,2 − V • φ for LaCl 3 (aq) and La(ClO 4 ) 3 (aq) are nearly the same, and similarly for NdCl 3 (aq) and Nd(ClO 4 ) 3 (aq), but for the corresponding Tb and Lu salts, the curves for the RCl 3 (aq) fall above those for their corresponding R(ClO 4 ) 3 (aq) at essentially all molalities.…”
Section: (Aq) and R(so )mentioning
confidence: 99%
See 1 more Smart Citation